Vom Folterzentrum der Militärdiktatur zum Ferienort Die Geschichte der "Villa Baviera" in Chile - Cwik, Christian; König, Hans-Joachim; Rinke, Stefan (Historamericana, 2022)
Under Augusto Pinochet, the "Colonia Dignidad" founded by the German itinerant preacher Paul Schäfer was a base of the Chilean military dictatorship. As "Villa Baviera" it continues to exist as a tourist destination. The transformation of a torture center into a holiday resort has received little attention. This source-based account examines the history of this settlement from a scholarly perspective for the first time.